PENGARUH STRUKTUR AUDIT, KONFLIK PERAN, KETIDAKJELASAN PERAN, PEMAHAMAN GOOD GOVERNANCE, GAYA KEPEMIMPNAN, BUDAYA ORGANISASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR (Studi Empiris Pada KAP di Semarang) - Adi Kurniawan, 13.05.52.0164; Alfasadun, Alfasadun (Students Journal of Accounting and Banking, 2017)
This study examined the influence of role conflict, role ambiguity, leadership style, organizational culture, and organizational commitment on the performance of auditors ( Empirical Study on Public Accounting Firm in Semarang ). This study used five independent variable and one dependent : Audit Structure, role conflict, role ambiguity, Understanding of good governance, leadership style, organizational culture, organizational commitment and performance of auditors. The population in this study is the auditor who worked on Public Accounting Firm in Semarang. The research sample was obtained through survey method on Public Accounting Firm in Semarang. Data collection techniques using questionnaires filled out by the respondents that tehÂ auditors. The total sample were obtained and used in the study was 46. The results obtained are Audit Structure, role conflict, role ambiguity, Understanding of good governance, leadership style and organizational culture does not affect the performance of auditors while organizational commitment affect the performance of auditors.Keywords: Audit Structure, Role Conflict, Role Ambiguity, Understanding of Good Governance, Leadership Style, Organizational Culture, Organizational Commitment, Performance of Auditors